TOKSISITAS Bacillus sphaericus H-5a5b (VCRC B42i) TERHADAP LARVA Culex quinquefasciatus - Salamun; Rosmanida; Ni’matuzzahroh; R.A. Samsumaharto (The East Java Biological Society, 1996)
Bacillus sphaericus H-5a5b is an entomoathogenic agent which showing high potency for vector control, highly specific to insect target, and do not produce any adverse environmental impact. Such agent would be promising for vector control in Indonesia. The present studies is aimed to observing the toxicity status of Bacillus sphaericus H-5a5b (VCRC B42) against Culex quiquefascitus larvae. The larvae of Culex quiquefascitus were reared under the laboratory conditions. The powder of VCRC B42 were prepared by Vector Control Research Centre (VCRC), India. Bioassays on VCRC B42 agains larvae of Culex quiquefascitus were also carried out under the laboratory conditions. The value of LD50 and LT50 for VCRC B42 were decided using probit analysis. The toxicity status was compared with standart of VCRC India. The result of the bioassays showed that the VCRC B42 was moderately toxic agains larvae of the Culex quiquefascitus. The value of LD50 for VCRC B42 was 0.058 mg/l and LT50 about 27 hours.